2021
DOI: 10.1038/s41598-021-81748-w
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of resveratrol or lactic acid bacterium improves lens elasticity

Abstract: A decrease in the elasticity of the ocular lens during aging is associated with loss of the accommodative ability of the eye, leading to presbyopia. Although near vision impairment is a social issue affecting the length of healthy life expectancy and productivity of elderly people, an effective treatment to improve near vision has not yet become available. Here we examined the effect of Enterococcus faecium WB2000, Lactobacillus pentosus TJ515, and resveratrol on lens elasticity in rats, where the stiffness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Both the short-term and long-term administration of resveratrol and WB2000 mitigated the increase in lens stiffness, whereas the administration of TJ515 alone decreased the lens stiffness with long-term, but not short-term administration. 79 These results indicate that the oral supplementation of an antioxidative diet could be a potential candidate to ameliorate near vision impairment encountered during presbyopia.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 89%
“…Both the short-term and long-term administration of resveratrol and WB2000 mitigated the increase in lens stiffness, whereas the administration of TJ515 alone decreased the lens stiffness with long-term, but not short-term administration. 79 These results indicate that the oral supplementation of an antioxidative diet could be a potential candidate to ameliorate near vision impairment encountered during presbyopia.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 89%
“…This is in contrast to the quite active research interest in presbyopia. In addition to the miotics and lipoic acid choline esters discussed at the roundtable, there have been reports on improved lens elasticity and accommodation from anti-oxidant supplementation, resveratrol, lactic acid bacteria or periocular warming [26][27][28]. A greater awareness of emerging alternatives to current visual aids may empower those with presbyopia in their discussions with HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…32) In a previous study, L. pentosus TJ515 produced more anti-inflammatory cytokines such as interleukin-10 (IL-10) and interferon-γ (IFN-γ) than the control stain L. pentosus JCM1558 in mesenteric lymph node cells. 32) Given that it has been reported that dietary supplementation with L. pentosus TJ515 and resveratrol could manage the progression of near vision impairment, 33) L. pentosus TJ515 taken orally could exert an action in the eye. Thus, L. pentosus TJ515 is expected to prevent retinal inflammatory diseases by regulating systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%